Critical load bus voltage control using DVR under system frequency variation - Jindal, A.; Ghosh, Arindam; joshi, A. (Elsevier S.A., 2008)
The paper discusses the voltage control of a critical load bus using a dynamic voltage restorer (DVR) in a distribution system. The critical load requires a balanced sinusoidal waveform across its terminals preferably at system nominal frequency of 50 Hz. It is assumed that the frequency of the supply voltage can vary and is different from the system nominal frequency. The DVR is operated such that it holds the voltage across the critical load bus terminals constant at system nominal frequency irrespective of the frequency of the source voltage. In case of a frequency mismatch, the total real power requirement of the critical load has to be supplied by the DVR. To compensate for frequency variation, the dc linkof the DVR is supplied through an uncontrolled rectifier that provides a path for the real power required by the critical load to flow. A simple frequency estimation technique is discussed which uses a moving average process along with zero-crossing detector. Through detailed analysis and simulation studies using PSCAD/EMTDC it is shown that the voltage is completely controlled across the critical load.